EXPRESSION AND CLINICAL CORRELATION OF PD-1/PD-L1 AND VE1(BRAFP.V600E) IN PEDIATRIC LANGERHANS CELL HISTIOCYTOSIS - sneha tandon; Sheila Weitzman; Brooklyn Joyce; Bryan Maguire; Derek Stephens; James Whitlock; Cynthia Hawkins; Bo-Yee Ngan; Oussama Abla (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Background: Langerhans cell histiocytosis (LCH) is an inflammatory myeloid neoplasm with a wide spectrum of clinical presentations. Programmed Cell Death-1 (PD-1) receptor and its ligand (PD-L1)   are overexpressed in LCH, but their clinical significance is unknown. We performed a clinical correlation study of PD-1/PD-L1 and VE1(BRAFp.V600E) expression in 131 children with LCH.